Kombinasi Metode Evaluation Based on Distance from Average Solution (EDAS) dan Rank Order Centroid (ROC) Dalam Pemilihan Konten Layak Tonton Untuk Anak Usia Dini - Ben Rahman; Isfauzi Hadi Nugroho; Rima Ruktiari Ismail; Rito Cipta Sigitta Hariyono; Nurul Mega Saraswati (Journal of Computer System and Informatics (JoSYC), 2023)
YouTube accommodates videos on almost any topic, including entertainment, guides, music, personal vlogs, news, short films, documentaries, and other variations. This allows users to access content according to their interests and needs without significant restrictions. However, the issue of unsuitable content for children on YouTube has become an increasingly prevalent topic of discussion. The main issues related to unsuitable content for children on YouTube involve videos containing inappropriate material, violence, abusive language, and false or misleading information. While efforts have been made by YouTube to address this issue, it remains a concern given the large number of videos uploaded every day. In selecting YouTube content for early childhood, there are several criteria, including safety feasibility, interesting animation, interactivity, educational value, and positive value. Thus, this research emphasizes the importance of the existence of a decision support system in helping with the selection of YouTube content suitable for children. Decision Support Systems (DSS) use data analysis methods and various algorithms to process available information and data. The author applies a combination of EDAS (Evaluation Based on Distance From Average Solution) and ROC (Rank Order Centroid) methods to select the most appropriate and safe YouTube content for young children. This approach is used to rank each assessed piece of content. This resulted in the YouTube content "Lagu Anak Indonesia Balita" getting the top rank on alternative A8 with a maximum value of 1.00000, making it highly recommended for early childhood.